أثر الترويج السياحي في سلوك السيّاح ورضاهم دراسة ميدانية في سورية(2007-2008) - طيّوب محمود; صقر محمد; منصور وائل (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تُعدُّ دراسة سلوك السياح ومعرفة درجة الرضا عن الخدمات المقدّمة لهم، من أهم المبادئ التي يقوم عليها التسويق السياحي الناجح، ويأتي الترويج السياحي بوصفه أحد أهم مكونات المزيج التسويقي الهادف إلى التأثير في قناعات السائح وقراره الشرائي بعد فهم وتحديد العوامل المؤثرة فيه، بحيث يمكن جذبه وتحفيزه بمختلف الوسائل المتبعة في عملية الترويج، ويهدف البحث إلى دراسة أثر الترويج السياحي في سلوك السياح بمختلف الشرائح والجنسيات، ومعرفة وسائل الترويج الأكثر تأثيراً وفعاليةً، وتقييم درجة الرضا عن الخدمات المقدمة لهم، عبر دراسة ميدانية شملت عينة من السياح القادمين إلى سورية حجمها 525 خلال الفترة (2007-2008)، ومن أهم النتائج التي وصلت إليها: عدم رضا السياح عن تناسب الخدمات المقدّمة لهم مع مستوى الأسعار، وعدم الرضا إزاء مستوى خدمات النقل المحلي وخدمات مكاتب السياحة والسفر، وتُشجِّع صفة الأمن والأمان على قرار السياح للسفر واختيار سورية بوصفها مقصداً سياحياً إذ بلغت الأهمية النسبية لهذا العامل 92%. Studying tourists’ behavior and measuring satisfaction degree about the provided services are the most important pillars of the successful tourist marketing. Tourist promotion is one of the most important components of marketing mixture used to influence tourist’s contentment and purchase decision after understanding and defining the affecting factors to attract and stimulate him by different tools of promotion. This study aims to specify the impacts of tourist promotion upon the behavior of tourist of different classes and nationalities. It also looks into the most effective means of promotion and evaluates the customer’s satisfactions for the provided services in a field study covered a sample of about 525 tourists carried on in Syria during 2007-2008. Main results are: Tourists were not satisfied about the relationship between the services and the prices, the services of both local transportation and travel tourist agencies. Security and safety in Syria encourage tourists to choose it as tourists’ destination with up to 92% of relative importance.